Association between Measures of Women’s Empowerment and Use of Modern Contraceptives: An Analysis of Nigeria’s Demographic and Health Surveys - Asaolu, Ibitola O.; Okafor, Chioma T.; Ehiri, Jennifer C.; Dreifuss, Heather M.; Ehiri, John E. (Frontiers in Public Health, 2017)
Background Women’s empowerment is hypothesized as a predictor of reproductive health outcomes. It is believed that empowered girls and women are more likely to delay marriage, plan their pregnancies, receive prenatal care, and have their childbirth attended by a skilled health provider. The objective of this study was to assess the association between women’s empowerment and use of modern contraception among a representative sample of Nigerian women. Methods This study used the 2003, 2008, and 2013 Nigeria Demographic and Health Survey data. The analytic sample was restricted to 35,633 women who expressed no desire to have children within 2 years following each survey, were undecided about timing for children, and who reported no desire for more children. Measures of women’s empowerment included their ability to partake in decisions pertaining to their healthcare, large household purchases, and visit to their family or relatives. Multivariable regression models adjusting for respondent’s age at first birth, religion, education, wealth status, number of children, and geopolitical region were used to measure the association between empowerment and use of modern contraceptives. Results The proportion of women who participated in decisions to visit their relatives increased from 42.5% in 2003 to 50.6% in 2013. The prevalence of women involved in decision-making related to large household purchases increased from 24.3% in 2003 to 41.1% in 2013, while the proportion of those who partook in decision related to their health care increased from 28.4% in 2003 to 41.9% in 2013. Use of modern contraception was positively associated with women’s participation in decisions related to large household purchases [2008: adjusted OR (aOR) = 1.15; 95% CI = 1.01–1.31] and (2013; aOR = 1.60; 1.40–1.83), health care [2008: (aOR = 1.20; 1.04–1.39) and (2013; aOR = 1.39; 1.22–1.59)], and visiting family or relatives [2013; aOR = 1.58; 1.36–1.83]. The prevalence of modern contraceptive use among women with need for contraception increased marginally from 11.1% in 2003 to 12.8% in 2013. Conclusion Although there were marked improvements in all measures of women’s empowerment between 2003 and 2013 in Nigeria, the use of modern contraceptives increased only marginally during this period. Beyond women’s participation in household decision-making, further research is needed to elucidate how measures of women’s empowerment interact with cultural values and health system factors to influence women’s uptake of contraceptives.